Certified Sustainable: The role of Tanzanian tea producers in Global Value Chains - (:unkn) unknown (My University, 2008)
During this current era of globalization, African agriculture is increasingly being included in global agrifood value chains. This focus on a global value chain has increased support for export driven agriculture, while diversifying the nature of crops cultivated for export. The traditional commodities of coffee, cotton, cocoa, and tea are still being promoted through these systems, while new crops such as horticulture and cut flowers are becoming more popular. With these new crops and supply chain management approach to global sourcing, some of the value-added practices such as processing and packaging are also moving into the African agricultural landscape. As such, these approaches are increasing demands for quality and as a result export agriculture has become more standards driven, with the regulatory frameworks of the WTO and Multi-national Recognition Agreements (MRAs) supporting increased use of techno-science as a means to regulate quality and production. As a whole, these practices are changing the shape of African agriculture for those who can afford to be included in the process. Who then are included in this process and who is excluded? This paper takes a look at a traditional export commodity, tea, and discusses the implications of involvement in value-based certification schemes on different types of producers in East Africa.
Keywords: African Research